Reversed Robin Hood Syndrome in the light of nonlinear model of cerebral circulation - Piechna, Adam; Cieślicki, Krzysztof (Zielona Góra: Uniwersytet Zielonogórski)
The brain is supplied by the internal carotid and vertebro-basilar systems of vessels interconnected by arterial anastomoses and forming at the base of the brain a structure called the Circle of Willis (CoW). An active intrinsic ability of cerebral vascular bed maintains constant Cerebral Blood Flow (CBF) in a certain range of systemic pressure changes. This ability is called autoregulation and together with the redundant structure of the CoW guarantee maintaining CBF even in partial occlusion of supplying arteries.
Keywords: cerebral blood flow; autoregulation; steal syndrome; Circle of Willis; computational fluid dynamics